2022
DOI: 10.1007/s00228-021-03260-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic quinolones and risk of retinal detachment III: a nested case–control study using a US electronic health records database

Abstract: Background Quinolones are popular antibiotics that are known for their potency, broad coverage, and reasonable safety. Concerns have been raised about a possible association between quinolones and retinal detachment (RD). Methods We conducted a nested case–control study using electronic health records (EHR) from the Health Facts® Database. The initial cohort included all patients who were admitted between 2000 and 2016, with no history of eye disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Moreover, a study examining the adverse drug event reports submitted to FAERS found a positive association of Moxifloxacin with RRD. 53 Conversely, other studies including a nationwide, registerbased cohort study from Denmark, 54 two case-control analyses from USA, 55,56 a retrospective cohort study using The Health Improvement Network database, 57 a self-controlled case series study of data from Hong Kong Clinical Data Analysis and Reporting System Database and Taiwan National Health Insurance Research Database, 58 a nested casecontrol study of Korean National Health Insurance Service National Sample Cohort data, 59 and a nested case-control study of electronic health records 60 found no association between oral FQ use and retinal detachment. In addition, few systematic reviews and meta-analyses [61][62][63] did not also find any association of development of RRD with the use of systemic FQs.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…Moreover, a study examining the adverse drug event reports submitted to FAERS found a positive association of Moxifloxacin with RRD. 53 Conversely, other studies including a nationwide, registerbased cohort study from Denmark, 54 two case-control analyses from USA, 55,56 a retrospective cohort study using The Health Improvement Network database, 57 a self-controlled case series study of data from Hong Kong Clinical Data Analysis and Reporting System Database and Taiwan National Health Insurance Research Database, 58 a nested casecontrol study of Korean National Health Insurance Service National Sample Cohort data, 59 and a nested case-control study of electronic health records 60 found no association between oral FQ use and retinal detachment. In addition, few systematic reviews and meta-analyses [61][62][63] did not also find any association of development of RRD with the use of systemic FQs.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…Of the targeted FQs, only moxifloxacin showed a positive disproportionality signal for retinal detachment. However, Taher et al [ 222 ] found no increased risk of retinal detachment within 30 days following FQs systemic administration.…”
Section: Side-effects Of Fqs and Underlying Mechanismsmentioning
confidence: 99%
“…Women were shown to be more at risk than men, while African Americans were found to be more at risk than Caucasians. There was also a five-fold risk in the youngest-age tertile (0–55), which decreased and became non-significant in the higher-age tertiles [ 222 ].…”
Section: Rational Use and Caution Of Modern Fqsmentioning
confidence: 99%
“…Many large cohort studies have showed conflicting results concerning the association between retinal detachment and FQs use. Further studies with additional information disclose the necessity of complementary studies to clarify these data [ 49 , 50 ].…”
Section: Potentially Life-threatening and Disabling Adverse Effectsmentioning
confidence: 99%
“…Muchos estudios de cohortes de gran envergadura han mostrado resultados contradictorios en cuanto a la asociación entre el desprendimiento de retina y el uso de FQs. Parece necesario realizar más estudios con información adicional para complementar estos datos [49,50].…”
Section: Gestión Y Advertencias De Seguridad En Relación Con Los Efec...unclassified